A conceptual framework for describing the innovation in teams - Hashmi, Arshia; Ishak, Shahibudin (2017)
This article aims to establish a framework that predicts innovation in teams.The Input-Process-Output (IP-O) model and Transformational leadership theory provide the foundation for this framework.According to I-P-O model, transformational leadership and team size work as input variables while teamwork quality as process variable that ultimately causes innovation as output variable.The relevant literature for this study has been searched by consulting many electronic databases like emerald, SAGE, Wiley online, Science Direct, Springer, JSTOR and Tailor & Francis.A number of keywords like transformational leadership, teams, innovation, team size, teamwork and teamwork quality have been used to specifically identify the concerned literature.So, the constructive overview and debate of earlier literature provides the interaction of three variables being the possible predictors of innovation.These variables are transformational leadership, team size and teamwork quality. At the end, the conclusion has been drawn with discussion about limitations and future implications